HTTP blocking in RU: bbc.com, facebook.com, instagram.com, medium.com (Russia) - Voidly (2026)
WARNING severity censorship detected in Russia. Confidence: 85%. Data sourced from CensoredPlanet.
Censorship Incident ID: RU-2026-0012
Keywords: censorship; RU; censorship; warning